Efektivitas Kombinasi Terapi Relaksasi Benson dan Pemberian Rebusan Jahe terhadap Intensitas Dismenore pada Mahasiswi S1 PGSD Angkatan 2023 Unissula Semarang - Faridatul Qoidah; Hernandia Distinarista; Apriliani Yulianti Wuriningsih; Sri Wahyuni (Journal of Health, Medical, and Psychological Studies, 2025)
Dysmenorrhea is a common menstrual disorder experienced by women of reproductive age and often interferes with daily and academic activities. Non-pharmacological management is increasingly recommended to minimize the side effects of long-term analgesic use. This study aimed to determine the effectiveness of a combination of Benson relaxation therapy and ginger decoction on the intensity of dysmenorrhea among undergraduate students of the Elementary School Teacher Education Program, Class of 2023, at Universitas Islam Sultan Agung Semarang. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group pretest–posttest. A total of 48 respondents were divided into intervention and control groups. The results showed that before the intervention, 91.7% of respondents in the intervention group experienced severe pain, while after the intervention, 79.2% experienced mild pain. Wilcoxon test results indicated a significant reduction in pain intensity in the intervention group (p=0.000). Mann-Whitney test results also showed a significant difference between the intervention and control groups (p=0.000). The combination of Benson relaxation therapy and ginger decoction was proven effective in reducing dysmenorrhea intensity.